Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

What is the value of the expression below when y=6y=6?
6y-1
6y−1


Sagot :

Answer:

The value of expression 6y-1 will be 35 when y=6.

Step-by-step explanation:

Given expression is:

6y - 1

We have to find the value of expression when y=6

Putting y=6 in the given expression

6*6 - 1

36 - 1

35

The value of the expression will be 35 for y=6

Hence,

The value of expression 6y-1 will be 35 when y=6.